Home as Found : Authority and Genealogy in Nineteenth-Century American Literature - Sundquist, Eric J.; Project Muse. (Baltimore : Johns Hopkins University Press, 1979)
Eric Sundquist takes four representative writers--James Fenimore Cooper, Henry David Thoreau, Nathaniel Hawthorne, and Herman Melville--and considers the way in which each grapples with the crucial issues of genealogy and authority in his works. From all four a common pattern emerges: the desire to revolt against the past is countered by the need to invoke or even repeat it. Sundquist's approach to the texts is psychoanalytic, but he does not attempt a clinical dissection of each writer; rather, he determines how personal crisis became material for engaging with larger questions of social and literary crisis.
"The home of my childhood": incest and imitation in Coopers' Home as found -- "Plowing homeward": cultivation and grafting in Thoreau and the Week -- "The home of the dead": representation and speculation in Hawthorne and The house of seven gables -- "At home in his words": parody and parricide in Melville's Pierre.
Part of Chapter 1 originally appeared as "Incest and Imitation in Cooper's Home as Found, '' 1977 by The Regents of the University of California, and is reprinted from Nineteenth-Century Fiction, Vol. 32, No. 3, pp. 261-84, by permission of The Regents
Description based on print version record.
Keywords: Psychoanalysis and literature; Families in literature; Authority in literature; American literature; Autorite dans la litterature; Psychanalyse et litterature; Familles dans la litterature; Litterature americaine -- 19e siecle -- Histoire et critique; Authority in literature; Psychoanalysis and literature; Families in literature; American literature -- 19th century -- History and criticism; Criticism, interpretation, etc; Electronic books